Syrian revolt : protestors at a crossroads - James M. Dorsey (2012)
After five months of mass anti-government protests and despite a brutal crackdown, opponents of Syrian president Bashar al Assad are struggling to contain sectarian strife, and prevent their demonstrations from turning violent. They need to unify their efforts to force political and economic change.